Strategi Public Relations Dalam Meningkatkan Brand Awareness Segari Terhadap Konsumen - Azizah Des Derivanti; Meisya Faradina Nurul Aulia (Jurnal Mahasiswa Kreatif, 2023)
In this modern era, it certainly has various kinds of changes, including a very significant technological speed. This is what leads an entrepreneur to innovate and have a very broad creativity in reaching digital markets to market their products. As an example, Segari reaches its consumers, where they market their products through an online application and can be opened anywhere and anytime. Currently companies must be able to provide various kinds of strategies so that their companies can be reached by the general public. Brand Awareness is the ability of a particular brand to display in the minds of consumers when they are thinking about a particular product group and how easy the product is to pronounce.